Regeneration procedures and mortality of Pinus radiata D. Don in the Southern Cape Province - Zwolinski, Janusz Boguslaw (Stellenbosch : Stellenbosch University, 2012)
Dissertation (Ph. D.) -- University of Stellenbosch, 1992.